Analisis Pengaruh Kompetensi Sumber Daya Manusia dan Teknologi Informasi terhadap Kinerja Pegawai di Kantor Kecamatan Merawang Kabupaten Bangka - Sekar Anggraini; M Andi Alfin Royan; Rizki Mardiansyah (Transformasi Manageria Journal of Islamic Education Management, 2025)
This research aims to assess the influence of human resource competence and the application of information technology on employee performance at the Merawang District Office. The method used in this research was descriptive and associative, involving 32 employees as research subjects. Data was collected through questionnaires distributed using the census method. Data analysis was carried out using multiple linear regression using SPSS version 26, and validity and reliability testing was carried out. The research results show that there is a significant influence of human resource competence and the application of information technology, both separately and simultaneously, on employee performance. It is hoped that the results of this research can encourage increased competence and use of technology among employees, so that performance and quality of service to the community can be improved.